Long-term Results After Oncoplastic Surgery for Breast Cancer: A 10-year Follow-up. Issue 1 (July 2018) - Clough, Krishna B.; van la Parra, Raquel F. D.; Thygesen, Helene H.; Levy, Eric; Russ, Elisabeth; Halabi, Najeeb M.; Sarfati, Isabelle; Nos, Claude
Abstract : Objective: The aim of this study was to evaluate the long-term oncologic outcome after oncoplastic surgery (OPS). Background: OPS combines wide tumor excision with reduction mammoplasty techniques thus extending breast conserving surgery to large tumors that might else be proposed a mastectomy. Little data are available about the oncologic results for breast conserving surgery of these larger tumors. Methods: From January 2004 until March 2016, a total of 350 oncoplastic breast reductions were prospectively entered into a database. Patients were included if their breast reshaping included a reduction mammoplasty with skin excision (Level 2 oncoplastic techniques). Results: Histologic subtypes were: invasive ductal carcinoma in 219 cases (62.6%), ductal carcinoma in situ (DCIS) in 88 cases (25.1%), and invasive lobular carcinoma in 43 (12.3%) cases. Seventy-three of the invasive cancers (27.9%) received neoadjuvant chemotherapy. The mean resection weight was 177 grams. The mean pathological tumor size was 26 mm (range 0–180 mm) and varied from 23 mm (4–180 mm) for invasive cancers to 32 mm (0–100 mm) for DCIS. Specimen margins were involved in 12.6% of the cases; 10.5% of invasive ductal, 14.7% of DCIS, and 20.9% of invasive lobular. The overall breast conservation rate was 92% and varied from 87.4% for DCIS to 93.5% for the invasive cancers. Thirty-one patients (8.9%) developed one or more postoperative complications, inducing a delay in postoperative treatments in 4.6% of patients. The median follow up was 55 months. The cumulative 5-year incidences for local, regional, and distant recurrences were 2.2%, 1.1%, and 12.4%, respectively. Conclusions: Oncoplastic breast reductions allow wide resections with free margins and can be used for large cancers as an alternative to mastectomy.